2018
DOI: 10.24908/pceea.v0i0.13081
|View full text |Cite
|
Sign up to set email alerts
|

Introducing and Sustaining Traditional Fabrication Methods in the Context of Teaching Prototyping for Engineering Design

Abstract: The introduction of Makerspaces across Canada has made it much easier for universities to provide engineering students the opportunity to “close the loop” on engineering design, by giving students the means to implement their projects. However, with the introduction of newer rapid prototyping technologies such as 3D printing, students forget or are unware that traditional fabrication technologies can often be more efficient then these new technologies, depending on the situation.This paper discusses the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…By fostering creativity and an awareness of the importance of trial and error, programs that incorporate makerspace education have shown a significant increase in student participation [9,14]. Courses taught in higher-education makerspaces meet long-standing design education goals [15,16].…”
Section: What Is a Makerspace?mentioning
confidence: 99%
See 2 more Smart Citations
“…By fostering creativity and an awareness of the importance of trial and error, programs that incorporate makerspace education have shown a significant increase in student participation [9,14]. Courses taught in higher-education makerspaces meet long-standing design education goals [15,16].…”
Section: What Is a Makerspace?mentioning
confidence: 99%
“…As the safety of students and staff is of paramount importance, the development of stringent safety protocols is necessary to ensure the proper functioning of the makerspace [9]. Workshops and protocols are organized to keep the equipment functional and mitigate the loss of makerspace knowledge after student graduation.…”
Section: Makerspace Safetymentioning
confidence: 99%
See 1 more Smart Citation